Human Papilloma Virus Infection in Patients with Male Accessory Gland Infection: Usefulness of the Ultrasound Evaluation - Rosita A. Condorelli; Enzo Vicari; Laura M. Mongioi; Giorgio I. Russo; Giuseppe Morgia; Sandro La Vignera; Aldo E. Calogero (International Journal of Endocrinology)
This study evaluated the ultrasound (US) features of 20 patients with MAGI and concomitant papilloma virus (HPV) infection compared to 20 patients with microbial (presence of Chlamydia trachomatis alone) MAGI and 20 patients with amicrobial (inflammatory) MAGI. Patients with HPV infection showed significantly (p<0.05) higher total prostate, seminal vesicles, and epididymal US signs (18.0 ± 2.0) compared to the other 2 groups (12.0 ± 4.0 versus 10.0 ± 3.0, resp.). In addition, patients with MAGI and HPV had a higher prevalence of complicated forms of MAGI [prostatovesiculitis (PV) and prostate-vesiculo-epididymitis (PVE)] and a higher frequency of the fibrosclerotic variant compared to the other groups (70.0 ± 10.0% versus 48.0 ± 5.0% versus 15.0 ± 10.0%). Moreover, HPV infected patients had a higher number of US criteria suggestive for MAGI in the periurethral region of the prostate compared to the other groups. In particular, the patients showed a higher ratio between periurethral and lobar US criteria distribution (5.0 versus 0.5). Finally, the seminal fluid concentration of CD45pos leukocytes (2.0 ± 0.2 versus 1.3 ± 0.3 versus 1.0 ± 0.3 mil/mL) was significantly higher and sperm progressive motility was significantly lower in these patients compared to other groups.